"Invisible Sportswomen 2.0" - Digging deeper into gender bias in sport and exercise science research: Author gender,editorial board gender, and research quality - Cowley, E. S.; Moore, S. R.; Olenick, A. A.; McNulty, K. L. (Women in Sport and Physical Activity Journal, 2023)
Objectives: Women are underrepresented as participants in sport and exercise science research, and most of the research is of low quality. To reduce the gender data gap, it is imperative to understand where this bias originates. The purpose of this study was (a) to evaluate the proportion of first and last author, and editorial board gender, and (b) to explore the association between gender and quality of female-specific research methods. Method: Studies exclusively investigating female participants (2014-2021) were extracted from a larger data set and updated through 2022. First author, last author, and editorial board gender were determined (e.g., from gender pronouns on institutional profiles, Google Scholar, and ResearchGate). Where applicable, study methodology was assessed by giving each study a quality score (0-1) based on key methodological considerations. Descriptive statistics were used to describe author and editorial board gender frequencies. Analyses of variance were used to investigate the associations between gender and female-specific methodological quality. Results: Within 438 female-only studies, data revealed a greater proportion of women first authors (55%) and men last authors (62%). There was an association between women authors (first, last, and both) and higher quality score for female-specific methods across all journals (p = .00-.04). The two lowest-ranked journals for quality score demonstrated worse gender parity within their editorial board (0%-12% women). Conclusions: The results from this study show that most female-only studies were senior authored by men. However, studies led by women had higher quality of female-specific methods. Future research is needed to explore gender distribution of senior academics.